Shifting Sustainable Mobility Agendas in Graz (Austria) and Hangzhou (China): The Multi-Level Process From Livable to Smart Cities - Luova, Outi (CSID Journal of Infrastructure Development, 2023)
Several studies on various urban sustainability projects have observed their conceptual and technological similarity throughout the world but, at the same time, identified significant divergences in their actual local framing and implementation. By analysing sustainable mobility policies in Hangzhou (China) and Graz (Austria) and changes in their agendas during a period of thirty years, this article contributes to that discussion with new empirical insights. The development trajectories in Hangzhou and Graz will be compared to identify similarities and divergences and to suggest future paths for comparative studies in sustainable urban mobility. The study draws inspiration from multi-level governance theory and places the analysis within critical global urban studies.